Biological functions of tear film. (August 2020) - Pflugfelder, Stephen C.; Stern, Michael E.
Abstract: Tears have a vital function to protect and lubricate the ocular surface. Tear production, distribution and clearance is tightly regulated by the lacrimal functional unit (LFU) to meet ocular surface demands. The tear film consists of an aqueous-mucin layer, containing fluid and soluble factors produced by the lacrimal glands and mucin secreted by the goblet cells, that is covered by a lipid layer. The array of proteins, glycoproteins and lipids in tears function to maintain a stable, well-lubricated and smooth optical surface. Tear factors also promote wound healing, suppress inflammation, scavenge free radicals, and defend against microbial infection. Disease and dysfunction of the LFU leads to tear instability, increased evaporation, inflammation, and blurred and fluctuating vision. The function of tear components and the consequences of tear deficiency on the ocular surface are reviewed. Highlights: The complex structure and composition of the tear film protects the cornea, promotes wound healing and maintains eye comfort and quality vision. The integrated lacrimal functional unit regulates tear production and maintains stability. Altered tear composition and stability in dry eye cause eye inflammation, corneal disease and blurred vision.